The impact of population growth on food production in Nigeria: An empirical analysis - Okpalanwabude, Ifeoma Florence (Humanities Horizon, 2025)
This study investigated the impact of population growth on food production in Nigeria. The study used secondary data spanning from 1980 to 2020 on food production, urban population, rural population, carbon dioxide emissions, government spending on agriculture, arable land, and agricultural. These data were analyzed using Autoregressive Distributed Lag (ARDL). The results revealed that urban population had a significant negative effect on food production in Nigeria for the period under study, among others. Based on the findings, it was recommended specifically that since population increases impacts negatively on food production, there is need to check population increases through measures like family planning, delayed marriages etc.